New gene-immunotherapy combining TRAIL -lymphocytes and EpCAMxCD 3 bispecific antibody for tumor targeting - Groth, Ariane; Salnikov, Alexey V.; Ottinger, Sabine; Gladkich, Jury; Liu, Li; Kallifatidis, Georgios; Salnikova, Olga; Ryschich, Eduard; Giese, Nathalia; Giese, Thomas; Momburg, Frank; Büchler, Markus W.; et al. (Clinical cancer research, 2012)
Purpose: To enhance T-cell responsiveness toward cancer cells, we overexpressed TRAIL in lymphocytes, as this death ligand induces tumor-specific apoptosis. To increase contact time of lymphocytes with tumor cells and thereby of TRAIL with its death receptors, lymphocytes were linked to the CD3 arm of bispecific antibody EpCAMxCD3, to guide the lymphocytes to tumor cells positive for the cancer stem cell marker EpCAM/ESA. Experimental Design: Lymphocytes were transduced with TRAIL lentivirus and the antitumor effect in presence and absence of EpCAMxCD3 was evaluated in vitro and in xenograft studies using epithelial cell adhesion molecule (EpCAM)-positive pancreatic and prostate cancer cells. Results: Compared with control lymphocytes, TRAIL-lymphocytes increased cytotoxicity and further induced expression of several apoptosis-related molecules. Cotransplantation of TRAIL-lymphocytes and tumor cells in mice or peritumoral injection of TRAIL-lymphocytes in larger xenografts retarded growth and induced apoptosis. Combination of TRAIL-lymphocytes with EpCAMxCD3 potentiated tumor eradication by enhancing antiapoptotic and antiproliferative signaling and by decreasing tumor vasculature. Intratumoral cyst formation was involved and associated with enhanced chemokine secretion and infiltration of mouse macrophages, suggesting contribution of an inflammatory host response. Most importantly, tumorigenicity of pancreatic cancer cells with cancer stem cell features resistant to conventional chemotherapy was strongly reduced. Conclusions: This gene-immunotherapeutic approach may be a new tool to support endogenous immune responses toward cancer even in its advanced stages. Clin Cancer Res; 18(4); 1028-38. ©2012 AACR.
Published first January 6, 2012
Gesehen am 12.06.2018